Pregnancy and Perinatal Outcomes of Patients With Prior Cesarean Section After a Single Embryo Transfer in IVF/ICSI: A Retrospective Cohort Study - Wang, Lin; Wang, Jing; Lu, Nan; Liu, Jiayin; Diao, Feiyang (Frontiers in Endocrinology, 2022)
Objective To study the influence of the previous cesarean section on the pregnancy outcomes and perinatal outcomes in single embryo transfer (SET) cycles in an in vitro fertilization/intracytoplasmic sperm injection-embryo transfer (IVF/ICSI-ET) setting compared to those with previous vaginal delivery (VD). In addition, the association between fertility outcomes and different cesarean scar defect (CSD) sizes was studied. Method This was a retrospective cohort study conducted in the Reproductive Center of the First Affiliated Hospital of Nanjing Medical University. A total of 4,879 patients with previous delivery history undergoing SET were included between January 2015 and April 2019. Patients were divided into the VD group and cesarean delivery (CD) group according to different modes of previous delivery. The primary outcome was live birth rate. The pregnancy outcomes of CD were analyzed as a subgroup and the relationship between pregnancy outcomes as well as the different sizes of CSD were explored by logistic regression analysis. Results There were no significant differences in live birth rate, clinical pregnancy rate, and miscarriage rate between the CD group and VD group. The incidence rates of pregnancy complications such as pregnancy hypertension, gestational diabetes mellitus, placenta abnormalities, premature rupture of membrane, and postpartum hemorrhage were similar in the two groups. Live birth rate was significantly lower in the CSD group (23.77% vs 37.01%, aOR: 0.609, 95% CI: 0.476-0.778) comparing to patients without CSD. There were also significant differences in clinical pregnancy rate (37.52% vs 47.64%, aOR: 0.779, 95%CI: 0.623-0.973) and miscarriage rate (34.55% vs 20.59%, aOR: 1.407, 95%CI:1.03-1.923). Large size CSD significantly decreased live birth rate (13.33% vs 26.29%, aOR: 0.422, 95%CI: 0.197-0.902) and clinical pregnancy rate (25.33% vs 40.09%, aOR: 0.503, 95%CI: 0.272-0.930) compared with small size CSD. Conclusion For women with previous cesarean sections, the pregnancy outcomes were similar to those with previous VD without increased perinatal complications following SET. The presence of CSD was associated with a marked reduction in live birth rate, especially in patients with large size CSD.